1973
DOI: 10.1161/01.res.32.4.524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flow and Pressure on Wave Propagation in the Canine Aorta

Abstract: Data on wave speed acquired from 20 anesthetized dogs showed that the thoracic aorta was essentially nondispersive for small artificially generated pressure waves traveling in the downstream or the upstream direction and having frequencies between 40 and 120 Hz. The amplitude of these waves decayed exponentially with the distance traveled. The attenuation was independent of frequency and pressure if the distance was measured in wavelengths. The logarithmic decrement of the downstream waves ranged between 0.7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 9 publications
4
22
0
Order By: Relevance
“…To our knowledge, this is the first study to have examined the relation between aPWV and TMP in vivo in man using a direct mechanical approach to modulate TMP, and the results reveal structural change in the properties of the aorta in hypertensive compared with normotensive subjects that cannot be appreciated from simple resting measures of aPWV. In normotensive subjects, the results demonstrate an increase in aPWV with increasing TMP, replicating results observed during mechanical manipulation of blood pressure in the canine aorta 6 and increase in blood pressure in humans achieved by infusion of angiotensin II. 10,26 By contrast, in hypertensive subjects, aPWV is seen to show little variation with TMP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, this is the first study to have examined the relation between aPWV and TMP in vivo in man using a direct mechanical approach to modulate TMP, and the results reveal structural change in the properties of the aorta in hypertensive compared with normotensive subjects that cannot be appreciated from simple resting measures of aPWV. In normotensive subjects, the results demonstrate an increase in aPWV with increasing TMP, replicating results observed during mechanical manipulation of blood pressure in the canine aorta 6 and increase in blood pressure in humans achieved by infusion of angiotensin II. 10,26 By contrast, in hypertensive subjects, aPWV is seen to show little variation with TMP.…”
Section: Discussionsupporting
confidence: 80%
“…3,4 By contrast, aPWV is closely associated with concurrent levels of blood pressure 5 implicating hypertension in the etiology of aortic stiffening. However, it is unclear whether the relation of aPWV to blood pressure is simply because of the aorta becoming stiffer as it is stretched by a higher transmural distending pressure (TMP, usually equal to intra-aortic blood pressure) 6 or whether it results from a structural change in the aortic wall associated with and contributing to a sustained elevation in blood pressure (ie, hypertension). Previous attempts to address this question by obtaining indirect estimates of isobaric stiffness have yielded conflicting results.…”
mentioning
confidence: 99%
“…The concurrence of the degree of dissipation demonstrates that wave dissipation in uniform elastic tubes has a strong similarity between the forward and backward directions. This finding agrees with that of Histand and Anliker (1973). They found that the ''wave travelling in either direction exhibited similar exponential decay patterns for their amplitudes''.…”
Section: Dissipation Of Wave Energysupporting
confidence: 88%
“…9,10 An acute elevation of blood pressure results in increased arterial stiffness in both animal models and in human subjects. 9,11,12 However, in hypertensive subjects it is not clear whether increased stiffness occurs as a result of elevated blood pressure or whether there is an intrinsic change in the elasticity of the arterial wall so that, when compared at the same operating pressure, it is stiffer than that in normotensive subjects. Previous studies to address this issue have examined the relationship of arterial pressure to diameter of the common carotid artery throughout the cardiac cycle with extrapolation to a common pressure.…”
mentioning
confidence: 99%